Optimized cooperative diversity for a three-node decode-and-forward relay channel - Kai-Kit, Wong; Elsheikh, Elsheikh Mohamed Ahmed (2007)
Due to space limitation, providing space diversity at mobile stations such as handsets or personal digital assistants (PDA) is problematic in mobile ad hoc networks (MANET). Recent studies, however, have shown that extraordinary diversity advantages can be obtained from a relay node in the proximity, which forwards the information from the source to the intended destination node via a diversity path. The diversity in reception can be easily translated into the benefits of increased achievable information rates or reduced outage probability. While previous works had demonstrated that remarkable gains can be achieved from simple fixed-relaying strategies when compared to without relaying, this paper takes an information-theoretic perspective to look into the optimal decode-and-forward (DF) single-relay scheme for 1) maximizing the mutual information between the source and the destination node given the instantaneous channel state information at all the participating nodes (CSIN), and 2) minimizing the outage rate probability given only the statistical channel information at the nodes (SCIN). In particular, we aim to find the optimal time-division between the direct transmission phase and the relaying phase, and the optimal power allocation for the two phases, for a three-node relay channel.